Nation-building and state support for creole languages: The cases of Haiti and the Seychelles - Cahill, Griffin (Working papers in Applied Linguistics and Linguistics at York, 2022)
Only two French-lexified creole languages possess de jure official status: Haitian (kreyòl aysisyen) in Haiti, and Seychellois (kreol Seselwa) in the Seychelles. This paper situates the past and contemporary sociolinguistics of Haitian and Seychellois in their respective homelands. The histories and politics of the two states are examined from their times as European colonies to their present-day as independent states. This will be followed by comparing the current state of the languages through three lenses: education, government, and popular discourse. The status of the creoles in each of those roles is discussed in relation to the other official languages of the states (French in both, along with English in the Seychelles.) The relationship between the creole languages and French is highlighted. I conclude with a discussion on the power of governmental support for creole languages generally, and potential lessons to be learned from the Haitian and Seychellois cases.